FORMAÇÃO DE PROFESSORES REFLEXIVOS: UMA ANÁLISE A PARTIR DA IMPLEMENTAÇÃO DA MODELAGEM MATEMÁTICA NOS ANOS INICIAISS - Juscelaine Martins de Freitas (2023)
ABSTRACT Continuing education needs to be seen as a permanent process in teaching practice, as a way of being constantly updated, seeking to improve knowledge in order to reflect its classroom practice, rethinking and even learning different forms of teaching, particularly mathematics . Therefore, it is necessary to investigate the teaching of mathematics in the early years, since at this level, teachers, in general, do not have specific training in mathematics. Thus, providing a differentiated view is a way to improve the quality of teaching and learning in this area and one possibility is to make the contents less abstract, working in an articulated way with reality, using real problems. In this context, this dissertation presented to the Graduate Program in Mathematics Education at the Federal University of Mato Grosso do Sul, presents Mathematical Modeling, which aims to investigate the continuing education of pedagogical teachers, highlighting the challenges and potentialities of the Modeling implementation process. Mathematics as a pedagogical alternative that can be used by teachers in the early years so that they can reflect their practice in Mathematics. The qualitative/interpretive research sought to relate the teacher's reflexivity and mathematical modeling. To this end, a continuing education course will be offered to teachers from preschool to fifth year of a public school with an emphasis on Mathematical Modeling and reflective practice and then the development of activities with Modeling will be observed with teachers developing Modeling activities during regular class time. We verified that among the challenges in developing Modeling in the early years is the time that students and teachers take to finish an activity and the planning factor being something more open and among the potentialities the possibility of reflection in their practice when this allows the your student an active participation. Keywords: Mathematics Education. Continuing training. Reflective Teachers. Teachers Pedagogues. Early Years.